Pedagogical Mediation in Virtual Learning Environments: Guidelines for Continuous Improvement - Bonilla Villalobos, Verónica (2025)
In response to the academic changes prompted by the COVID-19 pandemic, which forced the transition from a hybrid offer to a fully online one, a qualitative research was conducted using an action research (AR) design supported by digital ethnography. The objective was to create improvement actions for the teaching and learning process through elements of pedagogical mediation in the virtual environments of the Natural Resources Management program at the Universidad Estatal a Distancia de Costa Rica. The Kemmis and MacTaggart (1988) model was adapted to apply four stages: observation and diagnosis, planning, action and implementation, and evaluation of improvement actions. Various instruments and data collection techniques were employed, including focus groups, interviews, and peer evaluation, which were analyzed using Atlas ti8® software. Key stakeholders, including instructors, coordinators, experts from the Online Learning Program (PAL) and the Curriculum Support and Assessment of Learning Program (PACE) at UNED, as well as students, participated at different stages of the research. The findings led to the identification of elements of pedagogical mediation in both the literature and practice, which informed the development of a manual for instructors and virtual environment designers. This guide was organized into five categories: welcome, design, content, communication, and evaluation (see complete guide in annex). These categories aim to facilitate the creation of dynamic and interactive virtual learning environments for students, enabling instructors to design their virtual learning spaces in a more mediated and engaging manner. Continuous evaluation of virtual learning environments is essential, with methodologies and pedagogical strategies being adjusted to meet the emerging needs of students and technological trends.